Coupling of Single Molecule, Long Read Sequencing with IMGT/HighV-QUEST Analysis Expedites Identification of SIV gp140-Specific Antibodies from scFv Phage Display Libraries - Han, Seung Yub; Antoine, Alesia; Howard, David; Chang, Bryant; Chang, Woo Sung; Slein, Matthew; Deikus, Gintaras; Kossida, Sofia; Duroux, Patrice; Lefranc, Marie-Paule; Sebra, Robert P.; Smith, Melissa L.; et al. (Frontiers in Immunology, 2018)
The SIV/macaque model of HIV/AIDS pathogenesis is of great importance for understanding the role of antibody responses in prevention of HIV infection, especially that greater macaque immunoglobulin (IG) gene databases are being developed. We have previously reported the construction of a phage display library from a SIV-infected rhesus macaque (Macaca mulatta) using oligonucleotides primers based on human IG gene sequences. Our previous screening which relied on Sanger sequencing was inefficient and generated only a few dozen sequences. Here, we used the PacBio single molecule, real-time (SMRT) sequencing platform to generate thousands of highly accurate circular consensus sequencing (CCS) reads corresponding to full length scFv. CCS data were converted into FASTA files and analyzed through IMGT/HighV-QUEST (www.imgt.org). The results from the IMGT analysis were then submitted to statistical and clonotype analysis, also through the IMGT web portal. Overall, the library was very diverse, with 2569 different IMGT clonotypes called for 5238 IGHV sequences assigned to an IMGT clonotype. Within the library, SIV-specific antibodies represented a relatively limited number of clones, with only 135 different IMGT clonotypes called from 4594 IGHV assigned sequences. Our data did confirm that the IGHV4 and IGHV3 genes were the most abundant among the rhesus antibodies screened, and were even more enriched among SIV gp140-specific antibodies. The greatest distinctions were observed within the IGHD and IGHJ genes, in which one single gene, IGHD2-2 and IGHJ5-1, were represented in more than 85% of the total SIV-specific scFv assigned to an IMGT clonotype. Whereas the un-panned library repertoire showed a broad range of IGH CDR3 amino acid (AA) lengths with 78.29% of total antibodies having a IGH CDR3 of 17 AA or less, the vast majority of SIV gp140-specific antibodies (82.04%) had a IGH CDR3 of 20 AA. Only 174 IGKV and 588 IGLV clonotypes were identified for VL sequences associated with SIV gp140-specific VH. Considering that IMGT rhesus macaque V gene database can be rapidly updated, we believe that the combination of SMRT sequencing and the IMGT/HighV-QUEST querying tool will facilitate and expedite our understanding of polyclonal antibody responses during SIV infection.